英夫利昔单抗用于银屑病患者及其引起严重感染的 风险. (4th February 2019) - Yiu, Z.Z.N.; Ashcroft, D.M.; Evans, I.; McElhone, K.; Lunt, M.; Smith, C.H.; Walton, S.; Murphy, R.; Reynolds, N.J.; Ormerod, A.D.; Griffiths, C.E.M.; Warren, R.B.; et al.
Abstract : Linked Article:  Yiu et al. Br J Dermatol 2019;180 :329–337